2020
DOI: 10.1371/journal.pone.0236739
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low-cost culture medium for the rapid production of plant growth-promoting Rhodopseudomonas palustris strain PS3

Abstract: Rhodopseudomonas palustris PS3 is one of the purple phototrophic non-sulfur bacteria (PNSB), which have plant growth-promoting effects on various plants. To expand the scale of PS3 fermentation in a time-and cost-effective fashion, the purpose of this work was to evaluate the use of low-cost materials as culture media and to optimize the culture conditions via response surface methodology. Corn steep liquor (CSL) and molasses were identified as potential materials to replace the nitrogen and carbon sources, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Several works reported that it could promote plant growth by producing indole-3-acetic acid and 5-aminolevulinic acid ( Su et al., 2017 ), encourage resistance stress by producing peroxidase, and significantly affect rice rhizosphere bacterial communities ( Luo et al., 2019 ). The culture method of R. palustris has been investigated using 39.41 ml/L corn steep liquor and 32.25 g/L molasses at temperature 37.9 °C, pH 7.0, and 30% DO ( Lo et al., 2020 ). Other work also reported that the use of landfill leachate with 16.0 g/L total organic carbon and 1.1 g/L total nitrogen could use as medium growth of R. palustris ( Wang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several works reported that it could promote plant growth by producing indole-3-acetic acid and 5-aminolevulinic acid ( Su et al., 2017 ), encourage resistance stress by producing peroxidase, and significantly affect rice rhizosphere bacterial communities ( Luo et al., 2019 ). The culture method of R. palustris has been investigated using 39.41 ml/L corn steep liquor and 32.25 g/L molasses at temperature 37.9 °C, pH 7.0, and 30% DO ( Lo et al., 2020 ). Other work also reported that the use of landfill leachate with 16.0 g/L total organic carbon and 1.1 g/L total nitrogen could use as medium growth of R. palustris ( Wang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…For large-scale commercial manufacturing, optimizing the fermentation process is an essential step. To develop an optimal fermentation protocol for R. palustris PS3, we evaluated the use of low-cost materials as culture media and optimized the culture conditions via the response surface methodology [187]. We developed a novel medium for R. palustris fermentation with agro-industrial byproducts, i.e., corn steep liquor (CSL) and molasses, as nitrogen and carbon sources [187].…”
Section: Optimal Fermentation and Formulationmentioning
confidence: 99%
“…To develop an optimal fermentation protocol for R. palustris PS3, we evaluated the use of low-cost materials as culture media and optimized the culture conditions via the response surface methodology [187]. We developed a novel medium for R. palustris fermentation with agro-industrial byproducts, i.e., corn steep liquor (CSL) and molasses, as nitrogen and carbon sources [187]. In addition, we applied response surface methodology to determine the optimum fermentation process and the effectiveness of the new fermentation broth was verified by pot experiments [187].…”
Section: Optimal Fermentation and Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, culture condition has been identified as one of the most impacting factors for the photofermentative hydrogen production process. Lo et al reported that delaying in culture growth was observed as a result of unfavorable conditions [38]. Meeting favorable conditions for culture in a process like PF of glycerol to hydrogen it's a huddle needed to be addressed [24].…”
Section: Culture Cultivation and Conditionmentioning
confidence: 99%